RNA methylation in nuclear pre‐mRNA processing. (19th June 2018) - Covelo‐Molares, Helena; Bartosovic, Marek; Vanacova, Stepanka
Abstract : Eukaryotic RNA can carry more than 100 different types of chemical modifications. Early studies have been focused on modifications of highly abundant RNA, such as ribosomal RNA and transfer RNA, but recent technical advances have made it possible to also study messenger RNA (mRNA). Subsequently, mRNA modifications, namely methylation, have emerged as key players in eukaryotic gene expression regulation. The most abundant and widely studied internal mRNA modification is N 6 ‐methyladenosine (m 6 A), but the list of mRNA chemical modifications continues to grow as fast as interest in this field. Over the past decade, transcriptome‐wide studies combined with advanced biochemistry and the discovery of methylation writers, readers, and erasers revealed roles for mRNA methylation in the regulation of nearly every aspect of the mRNA life cycle and in diverse cellular, developmental, and disease processes. Although large parts of mRNA function are linked to its cytoplasmic stability and regulation of its translation, a number of studies have begun to provide evidence for methylation‐regulated nuclear processes. In this review, we summarize the recent advances in RNA methylation research and highlight how these new findings have contributed to our understanding of methylation‐dependent RNA processing in the nucleus. This article is categorized under: RNA Processing > RNA Editing and Modification RNA Processing > Splicing Regulation/Alternative Splicing RNA Interactions with Proteins and Other Molecules > Protein–RNA Interactions: Functional Implications Abstract : Messenger RNA (mRNA) undergoes a number of processing steps in the nucleus before it is exported to the cytoplasm, where it serves as a template for protein synthesis. The N 6 ‐methyladenosine (m 6 A) mark, and factors that write, read, and erase it, have been implicated in the regulation of mRNA processing.